Forced vital capacity less than 1: A mark for high-risk patients. Issue 2 (August 2018) - Warner, Rachel; Knollinger, Porter; Hobbs, Gerald; Lilly, Christa; Grabo, Daniel; Wilson, Alison
Abstract : BACKGROUND: Rib fractures (RFx) continue to be a source of morbidity and mortality. A RFx care pathway has been used based on forced vital capacity (FVC). The objective of this study was to test the hypothesis that deterioration of FVC to less than 1 after admission is a marker for high-risk patients and affects outcomes. METHODS: A retrospective study of patients enrolled in an RFx care pathway at a Level 1 trauma center from 2009 to 2014. All patients had an admission FVC greater than 1. 2 groups were analyzed: patients with a lowest inpatient FVC less than 1 (Group A) compared to patients with lowest inpatient FVC of 1 or greater (Group B). Complications [pneumonia, upgrade to the intensive care unit, readmission, and intubation] and demographics were examined. Patients without documented admission FVCs were excluded. p < 0.05 was considered significant. RESULTS: A total of 1, 106 patients were analyzed (Group A, 187; Group B, 919). Patients whose FVC dropped less than 1 (Group A) had a higher complication rate [15% (Group A) vs 3.2% (Group B); p < 0.001]. Rates of pneumonia, readmission, unplanned upgrade, and intubation were all significantly higher in Group A [pneumonia: 9% (Group A) vs 1.4% (Group B), p < 0.001; readmission: 4% (Group A) vs 1.7% (Group B), p = 0.04; upgrade; 3.7% (Group A) vs 0.2% (Group B), p < 0.001; intubation: 1.6% (Group A) vs 0.1% (Group B), p = 0.02]. Hospital length of stay was longer in Group A [10 days (Group A) vs 4 days (Group B), p < 0.001]. CONCLUSIONS: Forced vital capacity predicts complications in patients with RFx. Patients whose FVC falls less than 1 during admission are at high risk for pulmonary complications. Daily FVC testing for patients admitted with RFx can predict outcomes. Forced vital capacity less than 1 should be considered as a marker for complications. Once FVC drops less than 1, patients should be considered for increased interventions. Even if the patient has not yet clinically deteriorated, consideration for higher level of care is warranted. LEVEL OF EVIDENCE: Prognostic study, level III.